Endoscopic Transnasal Odontoidectomy for Ventral Decompression of the Craniovertebral Junction: Surgical Technique and Clinical Outcome in a Case Series of 19 Patients. Issue 1 (22nd October 2020) - Butenschoen, Vicki M; Wostrack, Maria; Meyer, Bernhard; Gempt, Jens
Abstract: BACKGROUND: Abnormalities and pathologies of the craniovertebral junction as well as space-occupying lesions of the odontoid process can result in myelopathy symptoms. A staged procedure with posterior stabilization and anterior transnasal endoscopic decompression is recently considered a less invasive alternative to the transoral approach. We present a considerably large case series focused on the operative technique and the long-term neurological clinical outcome. OBJECTIVE: To determine the safety and efficacy of odontoidectomy performed via an endoscopic transnasal approach. METHODS: We retrospectively reviewed all patients treated in our neurosurgical department from January 2009 to January 2020. Demographics, pre- and postoperative clinical status, and operative technique and complications were extracted and analyzed. RESULTS: In total, 22 transnasal operations were performed in 19 patients from January 2009 to January 2020. All but one patient underwent posterior C1-C2 instrumentation prior to the anterior transnasal computed tomography (CT)-navigated full-endoscopic decompression. The median duration of symptoms before surgery was 3 mo. Complications occurred in 1 patient who died from septic organ failure because of his initial diagnosis of osteomyelitis. Postoperative CT imaging showed sufficient decompression in 16 patients, and 3 patients underwent a transnasal endoscopic re-decompression (16%). CONCLUSION: Transnasal endoscopic odontoidectomy presents a safe procedure with a satisfying clinical and radiological postoperative outcome.